DENV-2 Circulation and Host Preference Among Highly Anthropophilic, Outdoor-Biting Aedes aegypti in Dar es Salaam, Tanzania - Frank S. C. Tenywa; Silvan Hälg; Haji Makame; Jason Moore; Osward Dogan; Harubu I. Mapipi; Jane J. Machange; Nasoro S. Lilolime; Lorenz M. Hofer; Lewis D. Batao; Tunu G. Mwamlima; Pie Müller; et al. (Viruses, 2025)
In Tanzania, dengue outbreaks have occurred almost annually over the past decade, with each new outbreak becoming more severe. This study investigated the prevalence of dengue virus (DENV) serotypes in the wild Aedes aegypti and their blood sources to determine human exposure risk in Dar es Salaam, Tanzania. A two-year longitudinal survey was conducted in the Ilala, Kinondoni, and Temeke districts of Dar es Salaam to sample Ae. aegypti mosquitoes using Biogents Sentinel trap (BGS), Prokopack aspiration, and Gravid Aedes trap (GAT). Collected mosquitoes were pooled in groups of 10 and tested for DENV1–4 serotypes using reverse transcription polymerase chain reaction (RT-qPCR). Blood meal sources were identified using an enzyme-linked immunosorbent assay (ELISA). Of 854 tested pools, only DENV-2 was detected and was found in all three districts: Temeke (3/371 pools), Ilala (1/206 pools), and Kinondoni (1/277 pools). Blood meal analysis showed a strong preference for humans (81%) as well as for mixed blood meals that contained human blood and other hosts (17%). Out of 354 collected hosts seeking Ae. aegypti, 78.5% were captured outdoors and 21.5% indoors. This study confirms the circulation of DENV-2 in Ae. aegypti populations, indicating a potential dengue outbreak risk in Tanzania. This study also demonstrates that xenomonitoring may be feasible in this setting. The mosquitoes’ strong preference for human hosts and predominance in outdoor settings pose challenges for dengue control efforts.